Immigration and the path-dependence of education: German-speaking immigrants, on-the-job skills, and ethnic schools in S\~ao Paulo, Brazil (1840-1920) - Bruno Gabriel Witzel de Souza (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2016)
This paper studies the impact of German-speaking immigrants on the path dependence of human capital accumulation in the State S\~ao Paulo, Brazil. Using a new dataset based on Almanacs from 1873 and 1888, we are able to test if (i) the cultural component, (ii) immigrants' on-the-job-skills, and (iii) their ethnic schools influenced the historical accumulation of human capital. No robust evidence was found for the first two explanations. On the other hand, for the 1910s, German schools had strong positive impacts on enrollment, not only for private, but also for state schools, a result which suggests the occurrence of spillover and contagion effects. Such impact tends, however, to dissipate over time and it does not survive for current educational performance. In addition, the paper shows that the pathdependence of education is conditional on the type of school: while there is a positive persistence in enrollment in private schools over the 20th century, enrollment in state schools depends negatively on its historical levels, reflecting convergence toward 100% enrollment rates in primary schooling. Furthermore, current stocks of human capital, measured by illiteracy and years of education, are shown to be strongly impacted by completion and enrollment in state schools back in the 1910s.
Keywords: 330